Heterogeneity among Mycobacterium avium complex species isolated from pulmonary infection in Taiwan - Hsiu-Mei Lin; Chin-Chung Shu; Chun-Hao Chen; Nan-Yu Chen; Jeng-How Yang; Chih-Hung Chen; Shih-Hong Li; Chih-Liang Wang; Chih-Teng Yu; Shu-Min Lin; Kuo-Chin Kao; Chung-Chi Huang; et al. (Microbiology Spectrum)
ABSTRACT Mycobacterium avium complex (MAC) is an emerging pathogen causing nontuberculous pulmonary infections globally. However, clinical treatment guidelines regard MAC as a single entity, recommending a universal anti-mycobacterial combination therapy. Our study aimed to distinguish species among MAC and investigate the antimicrobial susceptibility for the selection of optimal antimicrobial agents in Taiwan. Two hundred ninety-four consecutive sputum samples confirmed as MAC by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry were collected from 1 November 2015 to 31 August 2020 at Linkou Chang Gung Memorial Hospital in Taiwan. These isolates were identified through 16S rRNA gene, 23S rRNA gene, heat-shock protein 65 gene (hsp65), internal transcribed spacer, and beta subunit of RNA polymerase (rpoB) gene sequencing and phylogenetic analyses. Antimicrobial susceptibility testing (AST) was performed with 13 antimicrobial agents. The predominant pathogen identified was Mycobacterium intracellulare clade A (122/294, 41.5%), followed by M. intracellulare subsp. chimaera (87/294, 29.6%), M. intracellulare subsp. intracellulare (39/294, 13.3%), M. avium (35/294, 11.9%), and four other species (11/294, 3.7%). AST showed that clarithromycin and amikacin had high susceptibility rates against M. intracellulare clade A, M. intracellulare subsp. chimaera, M. intracellulare subsp. intracellulare, and M. avium, while linezolid and moxifloxacin exhibited higher resistance. The comparison of minimum inhibitory concentrations among species within the same antimicrobial agent showed variability in susceptibility. A diverse clonality of M. intracellulare might exist in MAC pulmonary infections in Taiwan. Among MAC species, M. avium exhibited multidrug resistance. Although international guidelines recommend macrolide, ethambutol, and rifampin for treating MAC pulmonary disease, our study highlights the importance of considering species identification and regional AST results when selecting anti-mycobacterial agents.IMPORTANCEThere are more than 10 (sub)species within the Mycobacterium avium complex. According to modern biotechnology, such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, it is still difficult to differentiate the complex into specific species precisely. We utilize concatenated multi-gene sequencing to classify this complex at the (sub)species level. Indeed, we encountered poorer treatment outcomes when facing Mycobacterium avium pulmonary infections compared to other species causing pulmonary infections. Individualized anti-mycobacterial therapy should focus on each species responsible for pulmonary disease.